2015
DOI: 10.1002/mabi.201500207
|View full text |Cite
|
Sign up to set email alerts
|

Nontoxic, Hydrophilic Cationic Polymers—Identified as Class of Antimicrobial Polymers

Abstract: Amphiphilic polycations are an alternative to biocides but also toxic to mammalian cells. Antimicrobially active hydrophilic polycations based on 1,4-dibromo-2-butene and tetramethyl-1,3-propanediamine named PBI are not hemotoxic for porcine red blood cells with a hemocytotoxicity (HC50) of more than 40,000 μg · mL(-1). They are quickly killing bacterial cells at their MIC (minimal inhibitory concentration). The highest found selectivity HC50 /MIC is more than 20,000 for S. epidermidis. Investigations on seque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
63
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(65 citation statements)
references
References 46 publications
1
63
0
Order By: Relevance
“…human erythrocyte) membranes generally contain higher proportion of zwitterionic lipids and possess cholesterol [32]. However, Strassburg et al have reported a class of non-hemocytotoxic hydrophilic polymers [35]. Although a variety of antibacterial polymers has been reported, the ability of polymers to disrupt surface established bacterial biofilms have been scarce.…”
Section: Accepted Manuscriptmentioning
confidence: 98%
“…human erythrocyte) membranes generally contain higher proportion of zwitterionic lipids and possess cholesterol [32]. However, Strassburg et al have reported a class of non-hemocytotoxic hydrophilic polymers [35]. Although a variety of antibacterial polymers has been reported, the ability of polymers to disrupt surface established bacterial biofilms have been scarce.…”
Section: Accepted Manuscriptmentioning
confidence: 98%
“…For example, the preparation of cationic polymers with hydrophilic, non-hemolytic antimicrobial properties was achieved by controlling the alkyl backbone length of tetramethyldiamines and dibromoalkanes in a polyaddition reaction. 18 Poly(2-methyloxazoline) with a quaternary ammonium terminal and a cleavable ester satellite terminal was also reported to exhibit bactericidal activity with low hemotoxicity.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, hydrophilic polycations often show a broader spectrum of activity. [9a] Moreover, they exhibit a by far less pronounced hemolytic activity against red blood cells than amphiphilic biocidal polymers and telechelic polymeric biocides. Both characteristics of hydrophilic polycations indicate a different mode of action, compared to telechelic biocidal polymers.…”
Section: Introductionmentioning
confidence: 99%
“…Both characteristics of hydrophilic polycations indicate a different mode of action, compared to telechelic biocidal polymers. [9a] Strassburg et al showed that the antimicrobial activity of hydrophilic polycations is additionally influenced by the end groups. [9a]…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation